2022
DOI: 10.3390/jmse10091187
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Dynamic Method for Conflict-Free Integrated Schedule Optimization in U-Shaped Automated Container Terminals

Abstract: Automated guided vehicles (AGVs) in the U-shaped automated container terminal travel longer and more complex paths. The conflicts among AGVs are trickier. The scheduling strategy of the traditional automated container terminal is difficult to be applied to the U-shaped automated container terminal. In order to minimize the handling time of all tasks and avoid AGV conflicts simultaneously in the U-shaped automated container terminal, this paper establishes a hybrid programming model for conflict-free integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Stage 5: The yard crane spreader vertically lowers container j to predetermined position. The time, distance, and speed of spreader running are 𝑑 𝑗 15 , 𝑑 𝑗 15 , 𝑣 𝑗 15 respectively.…”
Section: The Time Model Of Low Operation Platform For U-shaped Actmentioning
confidence: 99%
See 1 more Smart Citation
“…Stage 5: The yard crane spreader vertically lowers container j to predetermined position. The time, distance, and speed of spreader running are 𝑑 𝑗 15 , 𝑑 𝑗 15 , 𝑣 𝑗 15 respectively.…”
Section: The Time Model Of Low Operation Platform For U-shaped Actmentioning
confidence: 99%
“…The results indicated that U-shaped layout design had best performance. [15] provided a hybrid programming model for conflict-free integrated scheduling of quay cranes, AGVs, and double-cantilever rail cranes. The results showed the model could optimize multi-equipment scheduling and improve ACT efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The Problem Model Algorithm [29] Dynamic routing -Cluster reschedule [30] Railway scheduling with dynamic passenger demand MILP ALNS [31] Dynamic large-scale urban transportation Network Simulation [32] Dynamic job shop scheduling MIP GA [7] Dynamic routing with congestion Set Covering Batch assignment [33] Dynamic workload management for cranes -DSTP [34] Railway crew scheduling ILP CG + LR [35] Airline crew scheduling QP CG [36] A review of dynamic vehicle routing problems -- [37] Metro train scheduling dynamic passenger demand MILP LR [6] Crane scheduling DP Heuristic + Exact [8] Dynamic routing -B and P + CG [9] Dynamic job shop scheduling MILP PSO [38] Dynamic bus scheduling MIQP RO [39] Dynamic vehicle allocation in ridesharing MIQP ADP + LR [40] Dynamic job shop scheduling MDP DQN [41] Dynamic routing MILP DDD + LR [42] Dynamic routing MDP - [43] Dynamic job shop scheduling DRL PPO [44] Dynamic job shop scheduling MDP DQN [10] Dynamic routing MILP Heuristic…”
Section: Literaturementioning
confidence: 99%
“…Moreover, the re-optimized scheme takes effect as soon as possible to ensure continuous operation. In the literature, heuristic algorithms are widely used for solving dynamic scheduling problems, e.g., [6][7][8][9][10].Among them, the batch-based task assignment and the rolling-horizon are usually developed to cope with uncertainty and large-scale operations at terminals. Inspired by these approaches, we divide the task to be handled within a planning period into several batches.…”
Section: Introductionmentioning
confidence: 99%
“…In the U-Automated Container Terminal, the interaction positions between internal trucks and yard cranes have changed. Scholars [11][12][13] , taking…”
Section: Introductionmentioning
confidence: 99%